2010
DOI: 10.1016/j.bpj.2010.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Adhesion Tests against Functionalized Microspheres Arrayed on AFM Cantilevers Confirm Heterophilic E- and N-Cadherin Binding

Abstract: We assess the cross-reactivity of both cellular as well as recombinant E- and N-cadherins using functionalized bead arrays assembled on atomic-force-microscope cantilevers. This new approach builds upon and enhances the utility of a recently developed force probe that integrates a custom-built, horizontal atomic force microscope with micropipette manipulation. It enables us to test multiple biomolecular interactions of the same cell in a swift sequential or cyclic manner and thus to resolve subtle differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…When both N-cadherin and E-cadherin were present together in proximity, N-and E-cadherins formed heterodimers with an intermediate affinity of their respective homodimers 13 , whereas another study found the heterodimer formation to be still less frequent than homodimerization 14 . Interactions among type II cadherins are more complicated.…”
Section: Classical Cadherinsmentioning
confidence: 94%
“…When both N-cadherin and E-cadherin were present together in proximity, N-and E-cadherins formed heterodimers with an intermediate affinity of their respective homodimers 13 , whereas another study found the heterodimer formation to be still less frequent than homodimerization 14 . Interactions among type II cadherins are more complicated.…”
Section: Classical Cadherinsmentioning
confidence: 94%
“…The very basis of the model -the selectivity of cadherin homophilic binding -has been questioned: classical cadherins were reported to be able to interact extensively via heterophilic interactions (Shan et al, 2000;Shimoyama et al, 2000;Niessen and Gumbiner, 2002;Duguay et al, 2003;Patel et al, 2006;Prakasam et al, 2006;Ounkomol et al, 2010), and heterophilic adhesions have recently been demonstrated in a physiological context (Straub et al, 2011). Cells expressing similar levels of two different cadherins completely failed to sort in classical aggregates, and it was suggested that the previously reported cell sorting results could have been due to differences in cadherin levels.…”
Section: Critiquementioning
confidence: 99%
“…Like the clustered protocadherins, type I and type II cadherin binding is largely homophilic, 36 however, heterophilic interactions between cadherins of the same subtype have been observed in vitro. [37][38][39][40][41] Cadherins are found in dendrites, axons, and growth cones of young neurons. Live imaging studies suggest they preferentially cluster in pre and postsynaptic compartments at nascent synapses and then are maintained at pre and postsynaptic structures as synapses mature.…”
Section: The Classic Cadherinsmentioning
confidence: 99%